Kompetensi Dosen dan Penerapan Metode Pembelajaran pada Program Studi Ekonomi Syariah Universitas Pembangunan Nasional Veteran Jakarta - Syarif Ali; Pandapotan Simarmata (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The two main elements of a successful learning process are lecturer competency and learning methods. Changes in the field of education as well as changes in the mindset of students caused by technological developments, requires learning, in addition to having fun it should be effective and efficient. This study aims to: 1) describe the tendency of respondents' choice on criteria concerning indicators of competency and teaching methods; and 2) describe some characteristics that are important to be applied in Islamic economics study programs. This research is a qualitative descriptive (non experiment) using questionnaire in collecting data. with a population of 61 people who are students of the Sharia economics study program batch 2017. The results of the study show that the most doubtful criteria appear in each competency indicator (14), while the criteria “agree” to dominate respondents' answers to all learning methods (34). The development of lecturer prefessionalism on the depth and breadth of material is very important besides the learning method not only based on discussion, question and answer or reading task.